Pengaruh Motivasi Terhadap Disiplin Kerjapegawai Dimasa Pademi Covid 19 Di Dinaspekerjaan Umum Kabupaten Bengkulu Utara - Sumarni, Hania (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
This research realizes the goals of government organization Discipline of Civil Servants is absolutely necessary. In an organization in an effort to achieve goals, because after all the skills of an employee in carrying out his work without being accompanied by work motivation, his tasks given to him cannot be completed properly and on time. This research is entitled The formulation of the problem and the purpose of this research is, what is raised in this study is Is there an Influence of Motivation on Employee Work Discipline During the Covid 19 Period at the Public Works Office of North Bengkulu Regency and the major influences caused. The hypothesis in this study is that there is an influence of motivation on employee discipline at the Public Works Office of North Bengkulu Regency. To prove the hypothesis, Product Moment analysis is used, where data from the results of questionnaire processing is the main data in the analysis.To prove the magnitude of the relationship, the Determination formula is used. Furthermore, there is the influence of motivation in the Public Works Department of North Bengkulu Regency based on the results of research and discussion categorized as high, where from 60 respondents it shows that a high level of motivation is 73.0%. Medium 17.0% and low 10.0%. The level of Work Discipline of Employees at the Department of Public Works of North Bengkulu Regency can be said to be high where from the results of research which shows high work discipline is 57.25%, moderate is 22.8% and low is 20.0%. Based on Product Moment analysis, it is known that there is a relationship between Motivation and Work Discipline of Employees at the Public Works Office of North Bengkulu Regency, where r calculation results are 0.470 greater than r table 0.254 from the 95% confidence rate, so that the proposed hypothesis can be accepted while the magnitude of the relationship is based on determination analysis of 22.09%. The population in this study were 120 people and 60 people who became respondents to the questionnaire. Thus, apart from motivation, there are other variables that affect employee work discipline which are not examined.